The Impact of the Organizational Dimension in Behavioral Innovation and Strategic Innovation: An Analytical Study in Directorate of National Card Affairs - Wissam Kazem Haider; Amer Abdul Latif Kazem (Journal of Techniques)
This research aims to learn the range of impact of organizational dimension in behavioral innovation and strategy innovation. The targeted research sample is represented in the Directorate of the National Card.The discretional analytic method was used by using the questionnaire instrument to collect the data from the research population numbered (615) employees. A random sample numbered (220) employees was chosen. SPSSVer-24 program was used with statistical instruments and means such as (،Coefficient Analysis Arithmetic Mean،Standard Deviation،Difference Coefficient،Kendall's Collaboration coefficient ،Simple Linear Regression). The most important conclusions that are reached by this research is the existence of impact and collaboration relation between organizational dimension،behavioral innovation and strategic innovation.